Institutional Factors: Challenges For Coconut Sugar Small Enterprises Survival - Agus Arifin; Rakhmat Priyono; Goro Binardjo (Journal of Economics, Social, and Humanities, 2025)
Small enterprises often face various obstacles in developing and growing their businesses. Some of which are related to institutional factors. The aim of this research is to analyze institutional factorsmanagerial and technical skills and social capitalson coconut sugar small enterprise in Purbalingga. It used primary data that was collected from respondentsentrepreneurs of coconut sugar. The data collected was analyzed with competitive advantage approach by Porterthe five competitive forces modelto explain those factors. The model consists of five competitive forces: entry of competitors, threat of substitutes, bargaining power of buyers, bargaining power of suppliers, and rivalry among the existing players. The result shows that: 1) Coconut sugar enterprises have strong institutional factors, 2) Entrepreneurs can easily build this business with slight threat, 3) Coconut sap raw material is quite available but the quantity is uncertain, 4) The bargaining power of buyers is quite strong, especially in supressing product price, 5) Bargaining power of suppliers is also strong that is proven by the ease of marketing because of demand stability, 6) Competition among entrepreneurs is so high. They say that their competitors have more capitals but they have great optimism to win the competition. Their best strategy is to maintain quality, increase quantity, and also strengthen channels and networks.